A new species of Odontobdella Oka, 1923 (Erpobdelliformes: Salifidae), a macrophagous terrestrial leech from Central China - Yin, Zihan; Liao, Jinping; Li, Linbei; Xiang, Haiyang; Xiang, Dongqin; Liu, Zhixiao; Nakano, Takafumi (Zootaxa, 2025)
This paper describes a new species of macrophagous terrestrial leech distributed in Wuling Mountain area in Central China. On the basis of morphological and structural observation, mitochondrial cytochrome c oxidase subunit I (COI) gene sequence analysis and phylogenetic tree inference, this leech was identified as a new species of the genus Odontobdella in the family Salifidae, and named Odontobdella gaowangjiensis sp. nov. The main distinguishing features are: mid-body somites decem-annulate, c1 = c2 = c3 = c4 < b3 = b4 < c9 = c10 > c11 = c12 in adults, while in juvenile specimens, quinquannulate, b1 = b2 = a2 < b5 (c9 = c10) > b6; post-anal annuli present; eyespots in six pairs on somites II, III, IV and V; second pair on somite II largest; each of three myognaths bearing two conical stylets arranged in tandem, parallel to body axis; male gonopore in somite XI c11/c12 (slightly posterior to middle of somite XI b6), female gonopore in somite XII c11/c12 (slightly posterior to middle of somite XII b6), gonopores separated by ten annuli (= one full somite); atrial cornua heart-shaped, curved laterad; ovisacs tubular, extending to somite XVII. Type specimens were deposited in the Animal Collection, College of Biology and Environmental Sciences, Jishou University, Hunan, China.